2022
DOI: 10.17645/mac.v10i1.4767
|View full text |Cite
|
Sign up to set email alerts
|

Political Influencers on YouTube: Business Strategies and Content Characteristics

Abstract: Young media users increasingly engage with public affairs via social media such as YouTube, where content is increasingly produced by influencers who neither represent established professional news media nor political parties. Although the audience of these channels is already substantial in absolute terms and still growing enormously—making alternative influencers serious competitors to professional journalism—we still know little about their ways of attracting and monetizing audiences, the topics they emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
(48 reference statements)
0
4
0
1
Order By: Relevance
“…In addition, the study gave hints that most PSMI in the sample fund their activities just by their own resources. Most recently, a study of German- and English-speaking political YouTubers by Fischer et al (2022) showed that they start to build an economic income by advertising and building their brand through cross-media activities. However, they also emphasized that channels with a broader international audience appeared more successful in this respect than those limited to specific countries or language regions such as the few German-speaking countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the study gave hints that most PSMI in the sample fund their activities just by their own resources. Most recently, a study of German- and English-speaking political YouTubers by Fischer et al (2022) showed that they start to build an economic income by advertising and building their brand through cross-media activities. However, they also emphasized that channels with a broader international audience appeared more successful in this respect than those limited to specific countries or language regions such as the few German-speaking countries.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study is that it only included PSMI and their content that were nominated for the Hanns Seidel Foundation Award for Political Influencers 2021. In this respect, the sample does not necessarily represent the whole bandwidth of PSMI in Germany (see partly differences to Fischer et al, 2022) or for other countries. However, the sample showed that popular PSMI in Germany were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro, se ha indagado en la respuesta de los usuarios, caracterizada por la abundancia de mensajes hostiles y sexistas (Lima-Lopes, 2022). Asimismo, Fischer et al (2022) han estudiado el tema y la naturaleza del contenido, identificando tipologías como "burla partidista" y "educación participativa" en los vídeos analizados, mientras que Finlayson (2020) ha destacado el predominio de un estilo populista, un estilo de actuación política típico de los medios digitales.…”
Section: Propaganda Política Y Youtubeunclassified

Reaction and denial propaganda on social media

Hernández-Santaolalla,
Rubio-Hernández,
Fernández Gómez
et al. 2024
RCCI
“…Importantly, not only traditional news media use SNS to distribute news. So-called political influencers also gain an increasingly important role as a new generation of gatekeepers on SNS, as they report and share political information increasingly often and use their social reach to engage with politics and current affairs ( Bause, 2021 ; Fischer et al, 2022 ). In fact, political influencers were shown to have a positive effect on consumers’ response rate and the political agenda ( Curiel, 2020 ) as well as on political interest ( Schmuck et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%